The Issue of the Number of Priests in the USA and the UK in the Second Half of the 20th Century - Emelyanov Nikolai, archpriest (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия, 2016)
The author analyzes diﬀerent approaches towards evaluating the number of Roman Catholic and Protestant priests in the USA and in the Church of England. He considers the three narratives in the framework of which the problem under investigation has been posed: the “demography of the priesthood”, the “priest labor market” and the “territorial distribution of the clergy”. Schoenherr’s model (1993) is built upon the “organizational demography” approaches as well as upon the theory of rational choice and asks the question about what is going to happen to the population of the Catholic priests in the US in the nearest twenty years. Demographic tendencies for a long time prevalent lead to substantial changes in the overall structure of the population. The singling out of such tendencies and the determining factors behind them is extremely important for organizational planning. American Protestant denominations have toward the end of the 20th century found themselves in the situation of redundancy of priests. The research authored by Carroll (1980) is based upon the logic of the labor market and considers the interrelation between three values: number of the members of a Church; number of priests; number of churches. These values reﬂect the oﬀer and demand dynamics in the priest labor market. The researcher calculates the number of payments necessary to ensure the receiving of constant salary by a priest. He analyzes the factors determining the oﬀer and demand interrelation in the labor market. The research poses the question about the functions exercised by a priest. Still another tendency in the research on the number of priests exists in the Church of England; this tendency is connected with the issue of optimum territorial distribution of priests. The key research work here is the so-called “Paul report” (1964) which establishes the dependence of involvement in religious practices on the three following factors: number of those with full or part-time occupation in the sphere of pastoral activities; number of inhabitants of a given territory; number of churches in a given territory.